1985
DOI: 10.1159/000153551
|View full text |Cite
|
Sign up to set email alerts
|

Segregation Analysis of Ocular Refraction and Myopia

Abstract: Segregation analysis of ocular spherical refraction data using a unified model resulted in rejection of a Mendelian hypothesis of genetic transmission in nuclear families of both Japanese and European ancestries. Similar analyses of families which included at least 1 myope gave no evidence for the hypothesis that myopia is determined in part by a major gene. Most of the variation associated with ocular refraction, or with myopia, seems to be nongenetic in origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 9 publications
1
24
1
Order By: Relevance
“…Twin studies have shown high estimates of heritability for myopia [12][13][14] while family studies have resulted in consider ably lower estimates [15,16]. The present study uses, for the first time, a populationbased, unselected material for analysis of heritability in myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies have shown high estimates of heritability for myopia [12][13][14] while family studies have resulted in consider ably lower estimates [15,16]. The present study uses, for the first time, a populationbased, unselected material for analysis of heritability in myopia.…”
Section: Discussionmentioning
confidence: 99%
“…However, since this dominant transmission pattern was only evident in nine of the 36 families in Goldschmidt's cohort, it seems likely that other modes of inheritance of high myopia are more common than dominant inheritance. The failure to identify a major dominant myopia gene by segregation analysis36 is consistent with this view, although a recent study of the inheritance of corneal astigmatism37 suggests that this type of segregation analysis is not always capable of disclosing dominant gene effects.…”
mentioning
confidence: 84%
“…Family studies in both Asian [49,50,51,52] and Caucasian populations [49,53,54,55,56,57] have demonstrated that the parental refractive status plays an important role in the refractive status of their offspring.…”
Section: Pathological Myopiamentioning
confidence: 99%